Peliosanthes laotica (Asparagaceae), a new narrow-leaved species from Laos - Vislobokov, Nikolay A.; Romanov, Mikhail S.; Тanaka Noriyuki; Nuraliev, Maxim S. (Phytotaxa, 2023)
Peliosanthes laotica is described and illustrated as a new species from Laos (Bolikhamsai province). It is most similar to P. cupuliformis in floral structure, but differs by longer, narrowly elliptic to lanceolate leaf blade, pedicellate (vs sessile) flowers, which are longer and wider, and obconic ovary higher than 1 mm.